Temporal trend analysis of extreme precipitation: a case study of Konya Closed Basin - Meral Büyükyıldız; Cihangir Köyceğiz (Pamukkale University Journal of Engineering Sciences, 2019)
The changes in the intensity and frequency of extreme climatic events bring about many important problems in terms of social, economic and environmental. Especially, it is very important to inquire the influences of climate change on extreme precipitation. Spatial and temporal trends of extreme precipitation have been investigated by many researchers at global, regional and local scales in recent years. This study is about the temporal variability of extreme precipitation of 4 meteorology station (Konya, Karaman, Aksaray, Nigde) on Konya Closed Basin in Turkey. Trend analysis of extreme precipitations was conducted by means of the Spearman’s Rho (SR), Mann-Kendall (MK) and Innovative Şen Trend test. According to the results of trend methods, non-significant decreasing trends are observed in extreme precipitation data of Aksaray, Karaman and Nigde meteorology stations while non-significant increasing trend is shown only in Konya meteorology station.